Mobile-Based National University Online Library Application Design: Mobile-Based National University Online Library Application Design - Miftahul Anwar; Mohammad Iwan Wahyuddin; Winarsih Winarsih (Jurnal Mantik, 2020)
National university library services are still fairly manual because each process is still using paper book loan forms so there is no efficiency in the use of time and energy, besides the library extends the range of information provided to all national university students by building an application based on an Android-based library information system. In enhancing a process of development, an android- based library information system is built, using the system development life cycle (SDLC) method, which is an information system approach method used in making and developing applications. The goal is to achieve this research is to produce a library application that makes it easy for each book loan transaction to students can be done easily without any manipulation of making data that still uses forms. The desired result of this researcher is to make it easier for library members and their officers in making book loan transactions, making it easier for data processing